The foraging distribution and habitat use of chick-rearing snow petrels from two colonies in Dronning Maud Land, Antarctica - Honan, Eleanor Maedhbh; Wakefield, Ewan D.; Phillips, Richard A.; Grecian, W. James; Prince, Stephanie; Robert, Henri; Descamps, Sébastien; Rix, Anna; Hoelzel, A. Rus; McClymont, Erin L. (Marine Biology, 2025)
The polar sea-ice zones are highly productive and seasonal habitats that support large populations of vertebrate predators. In the Antarctic, snow petrels (Pagodroma nivea) are regarded as highly ice-dependant, yet knowledge of their habitat use and foraging distribution during the breeding period comes largely from ship-based observations. Snow petrels show sexual size dimorphism, and previous studies have demonstrated a degree of sexual segregation in habitat use in East Antarctica during the incubation period. Here, we characterise the movements, behaviour and habitat use of foraging snow petrels using bird movement and remotely sensed environmental data. We tracked snow petrels from two colonies in Dronning Maud Land, East Antarctica during early chick rearing in January to February 2022, a period of unusually rapid sea-ice retreat in the region. During the chick-rearing period, mean foraging range was c. 395 km and did not differ between the sexes. However, we found some evidence of differing habitat use between the sexes: males foraged more in areas of higher sea-ice concentration and over the continental shelf, while females utilized deeper waters and lower sea-ice concentrations. Sexes also diverged in their behavioural responses to both sea ice and depths, with males more likely to switch to foraging in areas of higher sea-ice concentrations than females and females more likely to switch to foraging in deeper waters than males. Although both sexes were more likely to forage at higher sea-ice concentrations, they also used areas with little or no sea ice. This contrasts with previous studies and may have been due to the unusual paucity of sea-ice cover during our tracking period.
Keywords: Dronning Maud Land; klimaendringer; marin biologi; ornitologi; petreller; sjøfugler; zoologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler

Variation in Antarctic Petrel Foraging Ecology: Not All Individuals Specialize on Krill - Descamps, Sébastien; Harris, Stephanie; Fluhr, Julie; Bustamante, Paco; Cherel, Yves; Trevail, Alice; Brault-Favrou, Maud; Patrick, Samantha (Frontiers in Marine Science, 2022)
Individual heterogeneity in foraging behaviour determines how individuals and populations respond to changes in the availability and distribution of resources. Antarctic krill Euphausia superba is a pivotal species in Southern Ocean food webs and an important target for Southern Ocean fisheries. Changes in its abundance could dramatically impact marine predators, with effects depending on the extent to which all individuals rely on krill as prey. The Antarctic petrel Thalassoica antarctica is a high latitude seabird thought to be dependent on krill in part of its breeding range. Here, by combining fine-scale GPS tracking of petrel foraging trips with diet data, we examined the level and consistency of inter-individual variation in foraging strategies in breeding Antarctic petrels in Dronning Maud Land, Antarctica, and assessed whether all individuals share a similar reliance on Antarctic krill. We found that Antarctic petrels showed high levels of repeatability in their diet and foraging movements at sea, indicating consistent individual differences in foraging strategies. During consecutive foraging trips, petrels tend to make trips of similar lengths and durations to reach similar terminal locations and to feed on similar prey. These individual differences in diet were spatially structured, with individuals travelling towards the west consuming a more fish-based diet. These different foraging tactics did not appear to be associated with different costs and/or benefits as adult body mass, chick survival and chick growth were unrelated to birds’ foraging movements and diet. Our results show that, even if a large part of the population may be dependent on krill, some individuals specialize on fish. Such inter-individual variation in foraging suggests that this population could be more resilient to changes in the marine environment, such as a decline in krill abundance or a shift in krill distributions.
Keywords: Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler; zoologi

Trophic and fitness correlates of mercury and organochlorine compound residues in egg-laying Antarctic petrels - Carravieri, Alice; Warner, Nicholas A; Herzke, Dorte; Brault-Favrou, Maud; Tarroux, Arnaud; Fort, Jérôme; Bustamante, Paco; Descamps, Sébastien (Environmental Research, 2021)
Understanding the drivers and effects of exposure to contaminants such as mercury (Hg) and organochlorine compounds (OCs) in Antarctic wildlife is still limited. Yet, Hg and OCs have known physiological and fitness effects in animals, with consequences on their populations. Here we measured total Hg (a proxy of methyl-Hg) in blood cells and feathers, and 12 OCs (seven polychlorinated biphenyls, PCBs, and five organochlorine pesticides, OCPs) in plasma of 30 breeding female Antarctic petrels Thalassoica antarctica from one of the largest colonies in Antarctica (Svarthamaren, Dronning Maud Land). This colony is declining and there is poor documentation on the potential role played by contaminants on individual physiology and fitness. Carbon (δ13C) and nitrogen (δ15N) stable isotope values measured in the females' blood cells and feathers served as proxies of their feeding ecology during the pre-laying (austral spring) and moulting (winter) periods, respectively. We document feather Hg concentrations (mean ± SD, 2.41 ± 0.83 μg g−1 dry weight, dw) for the first time in this species. Blood cell Hg concentrations (1.38 ± 0.43 μg g−1 dw) were almost twice as high as those reported in a recent study, and increased with pre-laying trophic position (blood cell δ15N). Moulting trophic ecology did not predict blood Hg concentrations. PCB concentrations were very low (Σ7PCBs, 0.35 ± 0.31 ng g−1 wet weight, ww). Among OCPs, HCB (1.02 ± 0.36 ng g−1 ww) and p, p’-DDE (1.02 ± 1.49 ng g−1 ww) residues were comparable to those of ecologically-similar polar seabirds, while Mirex residues (0.72 ± 0.35 ng g−1 ww) were higher. PCB and OCP concentrations showed no clear relationship with pre-laying or moulting feeding ecology, indicating that other factors overcome dietary drivers. OC residues were inversely related to body condition, suggesting stronger release of OCs into the circulation of egg-laying females upon depletion of their lipid reserves. Egg volume, hatching success, chick body condition and survival were not related to maternal Hg or OC concentrations. Legacy contaminant exposure does not seem to represent a threat for the breeding fraction of this population over the short term. Yet, exposure to contaminants, especially Mirex, and other concurring environmental stressors should be monitored over the long-term in this declining population.
Keywords: Dronning Maud Land; forurensning; miljøendringer; miljøgifter; ornitologi; petreller; sjøfugler

Interactive effects of body mass changes and species-specific morphology on flight behavior of chick-rearing Antarctic fulmarine petrels under diurnal wind patterns - Dehnhard, Nina; Klekociuk, Andrew R; Emmerson, Louise (Ecology and Evolution, 2021)
For procellariiform seabirds, wind and morphology are crucial determinants of flight costs and flight speeds. During chick-rearing, parental seabirds commute frequently to provision their chicks, and their body mass typically changes between outbound and return legs. In Antarctica, the characteristic diurnal katabatic winds, which blow stronger in the mornings, form a natural experimental setup to investigate flight behaviors of commuting seabirds in response to wind conditions. We GPS-tracked three closely related species of sympatrically breeding Antarctic fulmarine petrels, which differ in wing loading and aspect ratio, and investigated their flight behavior in response to wind and changes in body mass. Such information is critical for understanding how species may respond to climate change. All three species reached higher ground speeds (i.e., the speed over ground) under stronger tailwinds, especially on return legs from foraging. Ground speeds decreased under stronger headwinds. Antarctic petrels (Thalassoica antarctica; intermediate body mass, highest wing loading, and aspect ratio) responded stronger to changes in wind speed and direction than cape petrels (Daption capense; lowest body mass, wing loading, and aspect ratio) or southern fulmars (Fulmarus glacialoides; highest body mass, intermediate wing loading, and aspect ratio). Birds did not adjust their flight direction in relation to wind direction nor the maximum distance from their nests when encountering headwinds on outbound commutes. However, birds appeared to adjust the timing of commutes to benefit from strong katabatic winds as tailwinds on outbound legs and avoid strong katabatic winds as headwinds on return legs. Despite these adaptations to the predictable diurnal wind conditions, birds frequently encountered unfavorably strong headwinds, possibly as a result of weather systems disrupting the katabatics. How the predicted decrease in Antarctic near-coastal wind speeds over the remainder of the century will affect flight costs and breeding success and ultimately population trajectories remains to be seen.
Keywords: Antarktis; fôring; klimaendringer; ornitologi; petreller; zoologi; økofysiologi; økologi

An ocean of possibilities: antarctic petrel's foraging in the Southern Ocean - Tarroux, Arnaud; Fauchald, Per; Varpe, Øystein; Yoccoz, Nigel G; Descamps, Sébastien (Fram forum, 2021)
Keywords: Sørishavet; fôring; marin biologi; observasjoner; ornitologi; petreller; sjøfugler; zoologi

Antarctic petrels ‘on the ice rocks’: wintering strategy of an Antarctic seabird - Delord, Karine; Kato, Akiko; Tarroux, Arnaud; Orgeret, Florian; Cotté, Cedric; Ropert-Coudert, Yan; Cherel, Yves; Descamps, Sébastien (Royal Society Open Science, 2020)
There is a paucity of information on the foraging ecology, especially individual use of sea-ice features and icebergs, over the non-breeding season in many seabird species. Using geolocators and stable isotopes, we defined the movements, distribution and diet of adult Antarctic petrels Thalassoica antarctica from the largest known breeding colony, the inland Svarthamaren, Antarctica. More specifically, we examined how sea-ice concentration and free-drifting icebergs affect the distribution of Antarctic petrels. After breeding, birds moved north to the marginal ice zone (MIZ) in the Weddell sector of the Southern Ocean, following its northward extension during freeze-up in April, and they wintered there in April–August. There, the birds stayed predominantly out of the water (60–80% of the time) suggesting they use icebergs as platforms to stand on and/or to rest. Feather δ15N values encompassed one full trophic level, indicating that birds fed on various proportions of crustaceans and fish/squid, most likely Antarctic krill Euphausia superba and the myctophid fish Electrona antarctica and/or the squid Psychroteuthis glacialis. Birds showed strong affinity for the open waters of the northern boundary of the MIZ, an important iceberg transit area, which offers roosting opportunities and rich prey fields. The strong association of Antarctic petrels with sea-ice cycle and icebergs suggests the species can serve, year-round, as a sentinel of environmental changes for this remote region.
Keywords: Sørishavet; Weddellhavet; biologi; geolokalisering; havis; isberg; isfjell; klimaendringer; miljøendringer; ornitologi; petreller; sjøfugler; sjøis; økologi

Foraging tactics in dynamic sea-ice habitats affect individual state in a long-ranging seabird - Tarroux, Arnaud; Cherel, Yves; Fauchald, Per; Kato, Akiko; Love, Oliver P; Ropert-Coudert, Yan; Spreen, Gunnar; Varpe, Øystein; Weimerskirch, Henri; Yoccoz, Nigel G; Zahn, Sandrine; Descamps, Sébastien (Functional Ecology, 2020)
Abstract Individual heterogeneity in diet and foraging behaviour is common in wild animal populations, and can be a strong determinant of how populations respond to environmental changes. Within populations, variation in foraging behaviour and the occurrence of individual tactics in relation to resources distribution can help explain differences in individual fitness, and ultimately identify important factors affecting population dynamics. We examined how foraging behaviour and habitat during the breeding period related to the physiological state of a long-ranging seabird adapted to sea ice, the Antarctic petrel Thalassoica antarctica. Firstly, using GPS tracking and state-switching movement modelling (hidden Markov models) on 124 individual birds, we tested for the occurrence of distinct foraging tactics within our study population. Our results highlight a large variation in the movement and foraging behaviour of a very mobile seabird, and delineate distinct foraging tactics along a gradient from foraging in dense pack ice to foraging in open water. Secondly, we investigated the effects of these foraging tactics on individual state at return from a foraging trip. We combined movement data with morphometric and physiological measurements of a suite of plasma metabolites that provided a general picture of a bird's individual state. Foraging in denser sea ice was associated with lower gain in body mass during brooding, as well as lower level of energy acquisition (plasma triacylglycerol) during both brooding and incubation. We found no clear relationship between the foraging tactic in relation to sea ice and the energetic stress (changes in plasma corticosterone), energetic balance (β-hydroxybutyrate) or trophic level (δ15N). However, a shorter foraging range was related to both the energetic balance (positively) and the trophic level (negatively). Our results highlight a diverse range of foraging tactics in relation to sea ice in Antarctic petrels. While the various foraging tactics do not seem to strongly alter energetic balance, they may affect other aspects of Antarctic petrels' physiology. Future changes in sea-ice habitats can thus be expected to have an impact on the individual state of seabirds such as Antarctic petrels, which could ultimately affect their population dynamics. Nonetheless, strong individual heterogeneity in the use of sea-ice habitats by a typical pagophilic species might strengthen its resilience to environmental changes and in particular to forecasted sea-ice loss. A free Plain Language Summary can be found within the Supporting Information of this article.
Keywords: Sørishavet; fôring; havis; marin biologi; miljøendringer; observasjoner; ornitologi; petreller; sjøfugler; sjøis; smelting; zoologi